Exploring the association between indoor air pollution (IAP) and anaemia among pregnant women in India - Jenica Barnwal; Dilwar Hussain; Rakesh Chandra (PLoS ONE, 2026)
Background Anaemia during pregnancy in India persists despite policy attention and nutritional interventions. While its primary determinants are well-recognized, the association between indoor air pollution (IAP) and anaemia among pregnant women in India remains conspicuously under-explored. Methods This study examines the relationship between exposure to IAP and anaemia among pregnant women, using the National Family Health Survey (NFHS-5, 2019–21), with an analytical sample of 25,579 respondents. Descriptive statistics, chi-square tests, and multivariable logistic regression were used to assess the association between IAP exposure and anaemia, while accounting for socio-demographic, health, and behavioural characteristics. Results IAP was significantly associated with higher odds of anaemia (COR: 1.43, 95% CI: 1.36–1.51). Pregnant women who were younger, had lower levels of education, resided in rural areas, belonged to scheduled tribe communities, and poor wealth index household were more likely to be anaemic. Conclusion These findings suggest the need to integrate household energy transitions and indoor air quality improvements into maternal anaemia reduction strategies.